Nanostructured Antimony‐Doped Tin Oxide Layers with Tunable Pore Architectures as Versatile Transparent Current Collectors for Biophotovoltaics. (25th July 2016) - Peters, Kristina; Lokupitiya, Hasala N.; Sarauli, David; Labs, Mathias; Pribil, Mathias; Rathouský, Jiří; Kuhn, Alexander; Leister, Dario; Stefik, Morgan; Fattakhova‐Rohlfing, Dina
Abstract : Nanostructured transparent conducting oxide (TCO) layers gain increasing importance as high surface area electrodes enabling incorporation of functional redox species with high loading. The fabrication of porous TCO films, namely, antimony‐doped tin oxide (ATO), is reported using the self‐assembly of preformed ATO nanocrystals with poly(ethylene oxide‐ b ‐hexyl acrylate) (PEO‐ b ‐PHA) block copolymer. The high molar mass of the polymer and tunable solution processing conditions enable the fabrication of TCO electrodes with pore sizes ranging from mesopores to macropores. Particularly notable is access to uniform macroporous films with a nominal pore size of around 80 nm, which is difficult to obtain by other techniques. The combination of tunable porosity with a large conducting interface makes the obtained layers versatile current collectors with adjustable performance. While all the obtained electrodes incorporate a large amount of small redox molecules such as molybdenum polyoxometalate, only the electrodes with sufficiently large macropores are able to accommodate high amounts of bulky photoactive photosystem I (PSI) protein complexes. The 11‐fold enhancement of the current response of PSI modified macroporous ATO electrodes compared to PSI on planar indium tin oxide (ITO), makes this type of electrodes promising candidates for the development of biohybrid devices. Abstract : Nanostructured transparent conducting oxide layers with a tunable porosity are prepared via self‐assembly of antimony‐doped tin oxide nanoparticles and PEO‐ b ‐PHA polymer. The combination of adjustable pore sizes from 10 nm mesopores to 300 nm macropores with a large conducting interface makes the obtained layers versatile current collectors for bioelectronic devices incorporating large amounts of functional bioentities such as photosystem I.